Characterization of a Micro Beam Fabricated with 3D Technology Using Image Processing Algorithm - Ertugrul, Ishak (Current Nanoscience, 2020)
Background: This article presents a micro beam, fabricated using digital light processing (DLP), one of the additive manufacturing methods. The fabrication process is based on the projection micro stereolithography method. Objective: The micro beam, which can move in one direction (y-axis), was designed according to the specified criteria and fabricated. In the experiments carried out during the fabrication process, it showed the effect of the support structures on the fabrication of the micro beam. Methods: For the characterization process, the micro beam connected to the probe station is connected to a circuit board with cables attached to the electrical pads. The image processing algorithm has been developed to detect the displacement of the micro beam as a result of the characterization processes. The operating voltage was increased from 0V to 2V and incremented until fracture and deterioration in the structure of the micro beam were observed. Results: The micro beam was able to withstand distortion and breaks up to a maximum voltage of 10V. When 12V voltage was applied to the micro beam, fractures occurred in the arm. As a result of the characterization process, the maximum displacement of the micro beam was measured as 2.32 μm at 10V voltage. Conclusion: The characterization results indicated the usability of the image processing algorithm in 3D technology.
Keywords: DLP